2004
DOI: 10.2135/cropsci2004.1770
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Deep Root Production in Tall Fescue and Perennial Ryegrass

Abstract: The identification and selection of germplasm with improved drought tolerance will play an important role in developing turfs with better performance and persistence during drought stress periods. The objectives of the study were to: (i) determine the feasibility of simultaneously selecting plants with low‐shoot‐to‐high‐root ratios and increased root mass in lower sand profiles using flexible tubes under greenhouse conditions, and (ii) determine gain from two cycles of selection for increased root production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 19 publications
(31 reference statements)
3
53
0
1
Order By: Relevance
“…The results indicate a need for further investigation of the relation between the eff ects of drought on root growth and formation of the above-ground phytomass in interaction with intensity of the utilization of covers. Good prospects of breeding of species and varieties with a view to obtaining a larger root system in relation to resistance to drought and a higher production is confi rmed by Svačina et al (2014), Bonos et al (2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate a need for further investigation of the relation between the eff ects of drought on root growth and formation of the above-ground phytomass in interaction with intensity of the utilization of covers. Good prospects of breeding of species and varieties with a view to obtaining a larger root system in relation to resistance to drought and a higher production is confi rmed by Svačina et al (2014), Bonos et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the electrical capacitance by + 3.9% led to a production response almost two times higher (+ 8.1%). As for grass species a er selection, an increased size of the root system and subsequently also production of meadow fescue and perennial ryegrass is referred by Bonos et al (2004). An important factor in respect of grass species and drought may be the factor of multiple mowing, represented in the paper by 3-fold mowing "meadow" and 5-fold mowing "grazing" utilization.…”
Section: Introductionmentioning
confidence: 99%
“…La correlation positive entre la teneur en NDF et la dégradabilité des écotypes de F. arundinacea confirme cette idée. F. arundinacea présente une plus faible dégradabilité potentielle (a + b) in sacco (82,7%) que Lolium perenne, une graminée fourragère des pays tempérés (90,5 %) (Beever et Siddons, 1984 ;Bonos et al, 2004). Les produits de fermentation in vitro des écotypes de F. arundinacea : Malgré la teneur élevée en fibres, F. arundinacea a produit une forte proportion de propionate (234,7 µmol/mmol AGV totaux) comparable au mélange de ray grass et trèfle (244,3 µmol/mmol AGV totaux) (Mbanzamihigo et al, 2000).…”
Section: Discussionunclassified
“…Furthermore, rooting of grasses is influenced by agricultural management factors: most importantly, fertilization (Fairley 1985;Ennik et al 1980;Forde and Lorenzo 2001), mowing and grazing strategies (Evans 1971(Evans , 1972Ennik and Baan Hofman 1983;Deinum 1985;Dawson et al 2003), and grassland age (Van Eekeren et al 2008). Finally, rooting is influenced by genetic characteristics: several studies have reported genetic differences in root biomass between various grass species (Van Eekeren et al 2010;Cougnon et al 2013) and varieties of perennial ryegrass (Bonos et al 2004;Crush et al 2007), and in root weight of wild versus bred perennial ryegrasses (Crush et al 2009). These latter experiments (Bonos et al 2004;Crush et al 2007;Crush et al 2009) were conducted in tubes under controlled glasshouse conditions, and covered only a short time period.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, rooting is influenced by genetic characteristics: several studies have reported genetic differences in root biomass between various grass species (Van Eekeren et al 2010;Cougnon et al 2013) and varieties of perennial ryegrass (Bonos et al 2004;Crush et al 2007), and in root weight of wild versus bred perennial ryegrasses (Crush et al 2009). These latter experiments (Bonos et al 2004;Crush et al 2007;Crush et al 2009) were conducted in tubes under controlled glasshouse conditions, and covered only a short time period.…”
Section: Introductionmentioning
confidence: 99%